PENGARUH PEMAKAIAN PENYANGGA PERUT TERHADAP NYERI PUNGGUNG IBU HAMIL TRIMESTER III - Kasuma Puri Zuryani; Dewi Nopiska Lilis; Suryani Suryani; Yuli Suryanti (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Back pain is one of the problems that pregnant women often complain about TM III. The prevalence of low back pain in pregnant women almost occurs between 24% to 90% of pregnant women. Research conducted on pregnant women in various regions in Indonesia found a percentage of 60-80% of pregnant women who experience back pain complaints This study is a pre-experimental quantitative study with a one group pretest-posttest design which aims to determine the effect of using an abdominal brace on back pain in third trimester pregnant women at the Kenali Besar Public Health Center in 2022. The study population was all third trimester pregnant women who visited the MCH Poly room. in January-March 2022 totaled 191 pregnant women. A sample of 30 respondents was taken by purposive sampling. This research was conducted from January to June 2022. Data analysis was carried out univariate and bivariate with the Wilcoxon test. The results of the univariate analysis before being given an abdominal brace the average pain scale was 5.90 and after being given an abdominal brace the average pain scale was reduced to 3.83. The results of the bivariate analysis showed that there was an effect of the use of abdominal support on back pain in third trimester pregnant women and obtained p-value = 0.000 (p < 0.05). It is hoped that this research can add references for officers and health centers on how to reduce back pain complaints of pregnant women in the third trimester, with nonpharmacological techniques, namely the use of abdominal supports.